DEVELOPING READING MATERIALS TOWARD CRITICAL DISCOURSE APPROACH (CDA) IN READING COMPREHENSION OF EFL LEARNERS - Prasetyaningsih, Rahayu (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2017)
Reading comprehension is commonly implemented in classroom only focus on language features without any interact with the written text in meaningful ways. Some teachers guide their students in analyzing linguistics structure or new vocabulary items in reading class, while reading actually not only focus on those activities. By reading, the learners as readers should also consider about the implicit meaning of the text and the way the writers express their ideas and thoughts toward a particular topic. Nabi. AEbrahimi and Ali Rahimiâ€™s article â€œToward a more efficient EFL reading comprehension classroom environment: The Role of content and critical readingâ€ in 2013 clearly state that most of EFL teachers were often to select the reading text which is only present the survival or without involving the general interest material for their students. They also state that, in selecting the reading passage the teachers should contextually such as social, discursive and textual. Ebrahimi and Rahimiâ€™s research was conducted to investigate the effect of a change in reading content and in structure but also lot of enjoyment and information of particular topic could be gained in order to improve their knowledge in many kinds of reading text which is teaching reading via a Critical Discourse Approach (CDA) framework on studentsâ€™ perceptions of their reading classroom environment. But, they did not provide some criteria toward a good reading passage and close to the contextual meaning for the students. In order to help teachers in selecting or developing their own reading passage which is involved some social aspects, latent message of the text and also writersâ€™ ideologies and thoughts, the writer suggest that EFL teachers should consider about some criteria deal with a good reading passage to enrich students awareness that a reading passage not only study about words and interesting.